PENGARUH LINGKUNGAN KERJA FISIK DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DEPARTEMEN FINANCE & TREASURY PADA PT SICEPAT EKSPRES INDONESIA JAKARTA SELATAN - Andriani, Meilisa; Hindriari, Reni (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the physical work environment and work motivation on employee performance. This research was conducted by analyzing the performance of employees of the Finance & Treasury Department at PT. SiCepat Express Indonesia, South Jakarta. Both partially and simultaneously. This research model uses associative quantitative research methods. In this research there are 3 variables, namely the physical work environment (X1) and work motivation (X2) which are independent variables and employee performance (Y) is the dependent variable. The objects of this research are employees of the Finance & Treasury Department at PT. SiCepat Ekspress Indonesia as many as 79 people. The sampling technique uses a population research sample in calculations up to an error rate of 5% so that the sample studied was 79 respondents. Data analysis used in this research uses classical assumption tests, simple and multiple linear regression tests and also hypothesis testing. Based on the SPSS Version 25 test results from the tests that have been carried out, it is known that the physical work environment and work motivation simultaneously influence employee performance. The research results show that from the t test results of the physical work environment variable (X1) on employee performance (Y) it was obtained that t_count was 7.742 > t_table 1.990 and the significance value was 0.000 < 0.05, and the t test results of the work motivation variable (X2) on employee performance ( Y) is obtained at t_count 7.520 > t_table 1.990 and a significance value of 0.000 < 0.05. Based on the results of the f test (simultaneous) obtained at f_count 116.35 > f_tabel 3.12 and a significance value of 0.000 < 0.05 and analysis of the coefficient of determination (R²) obtained a result of 0.747 (74.7%) so it can be concluded that the work environment physical (X1) and work motivation (X2) have a positive and significant effect on employee performance (Y).